Immunoselected STRO-3+ mesenchymal precursor cells reduce inflammation and improve clinical outcomes in a large animal model of monoarthritis. Issue 1 (December 2017) - Abdalmula, Anwar; Dooley, Laura; Kaufman, Claire; Washington, Elizabeth; House, Jacqueline; Blacklaws, Barbara; Ghosh, Peter; Itescu, Silviu; Bailey, Simon; Kimpton, Wayne
Abstract Background The purpose of this study was to investigate the therapeutic efficacy of intravenously administered immunoselected STRO-3 + mesenchymal precursor cells (MPCs) on clinical scores, joint pathology and cytokine production in an ovine model of monoarthritis. Methods Monoarthritis was established in 16 adult merino sheep by administration of bovine type II collagen into the left hock joint following initial sensitization to this antigen. After 24 h, sheep were administered either 150 million allogeneic ovine MPCs (n = 8) or saline (n = 8) intravenously (IV). Lameness, joint swelling and pain were monitored and blood samples for leukocytes and cytokine levels were collected at intervals following arthritis induction. Animals were necropsied 14 days after arthritis induction and gross and histopathological evaluations were undertaken on tissues from the arthritic (left) and contralateral (right) joints. Results MPC-treated sheep demonstrated significantly reduced clinical signs of lameness, joint pain and swelling compared with saline controls. They also showed decreased cartilage erosions, synovial stromal cell activation and angiogenesis. This was accompanied by decreased infiltration of the synovial tissues by CD4+ lymphocytes and CD14+ monocytes/macrophages. Over the 3 days following joint arthropathy induction, the numbers of neutrophils circulating in the blood and plasma concentrations of activin A were significantly reduced in animals administered MPCs. Conclusions The results of this study have demonstrated the capacity of IV-administered MPCs to mitigate the clinical signs and some of the inflammatory mediators responsible for joint tissue destruction in a large animal model of monoarthritis.